Isolat protein kacang tunggak termodifikasi melalui jenis dan konsentrasi bahan kimia - Choirul Anam; Emmy Hamidah; Dian Eka Kusumawati; Istiqomah Istiqomah; Mariyatul Qibtiyah; Ana Amiroh (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Cowpea is a type of legume that contains a lot of protein. One of the uses of cowpea as a food ingredient is protein isolate. The purpose of this study was to determine the type and concentration of chemicals suitable for cowpea protein isolate as well as its physical and chemical properties. Implementation of modified cowpea protein isolate was divided into three stages. The first stage is to determine the best results from the addition of certain types and concentrations of chemicals: a) CH3COOH (3%, 5%, 7%); b) CaSO4 (0.25%; 0.30%; 0.35%) and c) MgSO4 (0.25%; 0.30%; 0.35%). The second stage is to combine each of the best treatments. There are three treatments, namely treatment A is the addition of the best CH3COOH concentration with the best CaSO4 concentration. Treatment B is the best concentration of CH3COOH and the best concentration of MgSO4. Treatment C was the best concentration of CaSO4 and the best concentration of MgSO4. The third stage is the analysis of the physical and chemical properties of the treatment combinations formed. Each treatment was replicated three times. The data obtained were then analyzed descriptively. The results of the analysis are presented in the form of tables and histograms. The best treatment of chemically modified cowpea protein isolate was in treatment C (addition of 0.35% CaSO4 and 0.35% MgSO4), which had a gel strength texture of 13.87 gram force/0.1mm; with a water content of 81.04%; ash 6.77%; and protein 92.53%; and has the highest protein solubility at pH 8 of 22.47 mg/g.